Smartphone Use Intensity and Stress Impact on Adolescent Sleep Quality: A Correlation Study: Intensitas Penggunaan Smartphone dan Dampak Stres Terhadap Kualitas Tidur Remaja: Sebuah Studi Korelasi - Sugiono; Yenda Mei Rahmawati (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative cross-sectional study investigated the relationship between smartphone use intensity, stress levels, and sleep quality among 77 tenth-grade students from SMK Negeri 2 Sewon Bantul. Employing proportional random sampling, the study revealed a significant correlation between smartphone use intensity and sleep quality (p < 0.05), as well as stress and sleep quality (p < 0.05). These findings underscore the impact of smartphone usage and stress on adolescent sleep quality, highlighting the need for targeted interventions to mitigate potential negative outcomes and promote healthier technology habits among adolescents. Highlights: Adolescent Smartphone Dependency: Investigating the intensity of smartphone use among adolescents in a school setting. Stress and Sleep Relationship: Identifying the significant link between stress levels and sleep quality in students. Implications for Intervention: Highlighting the need for targeted strategies to address smartphone-related stress and promote healthier sleep patterns among adolescents. Keywords: Smartphone use, Stress, Sleep quality, Adolescents, Correlation study